Implementing experiential learning-based problem-based learning to improve fifth-grade IPAS learning outcomes on sound sources - Yulia Fitri Astutik; Belinda Dewi Regina (Jurnal Pendidikan Profesi Guru, 2025)
This classroom action research examined whether experiential learning-based problem-based learning (PBL) improves fifth-grade students’ IPAS learning outcomes on the topic of sound sources at SDN Ngaglik 01, Batu City, Indonesia. Twenty-six students participated in two action cycles (planning, action, observation, reflection), each consisting of two meetings. Achievement was measured using end-of-cycle tests, and observations informed reflection and revision. Learning outcomes improved from Cycle 1 to Cycle 2: the class mean rose from 72 to 83, mastery increased from 38.5% (10/26) to 88.5% (23/26), the highest score improved from 88 to 100, and the lowest score increased from 68 to 77. Overall, embedding authentic hands-on experiences in PBL helped students engage with problems, construct concepts, and demonstrate better understanding in IPAS lessons in a supportive collaborative setting.